Storage organization and indexing in a web warehouse - Qin, Feng Qiong (2010)
As the World Wide Web grows rapidly to become the largest and the most popular source of readily available information, it is increasingly important to be aware of information on the Web that may impact a business organization during critical decision making. Most existing search engines that support keyword queries do not allow efficient and sophisticated retrieval of web information. The WHOWEDA web warehousing project aims to harness useful web information for critical decision making by supporting efficient web queries.